1991
DOI: 10.1677/joe.0.1310401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of follicular fluid and inhibin immunoneutralization on FSH-induced preovulatory follicle growth in the ewe

Abstract: The potential direct ovarian effects of immunoneutralization of inhibin, which increases, and follicular fluid treatment, which inhibits, follicle development in normal ewes was investigated in a sheep model in which endogenous FSH and LH secretion was suppressed thus removing any potential effects of treatment-induced alterations in endogenous FSH or LH secretion. Eighteen Welsh Mountain ewes were treated with two agonist implants containing 3.3 mg buserelin giving a total of 6.6 mg buserelin per animal. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
(61 reference statements)
0
10
1
3
Order By: Relevance
“…As such, the study provides evidence that long-term exposure to inhibin antibodies may have direct effects on granulosa cell function that are not mediated by changes in pituitary FSH secretion. This evidence contrasts with a previous study in which acute exposure to exogenous inhibin (oFF) or inhibin antiserum had no effect on FSH-induced follicular growth in gonadotrophin-releasing hormone (GnRH) agonistsuppressed sheep (McNeilly et al 1991). However, other studies (Cahill et al 1985a,b) have shown that exogenous inhibin (oFF) can reduce gonadotrophin-induced follicle development in both intact and hypophysectomized ewes, findings which are more supportive of a direct ovarian action of inhibin.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…As such, the study provides evidence that long-term exposure to inhibin antibodies may have direct effects on granulosa cell function that are not mediated by changes in pituitary FSH secretion. This evidence contrasts with a previous study in which acute exposure to exogenous inhibin (oFF) or inhibin antiserum had no effect on FSH-induced follicular growth in gonadotrophin-releasing hormone (GnRH) agonistsuppressed sheep (McNeilly et al 1991). However, other studies (Cahill et al 1985a,b) have shown that exogenous inhibin (oFF) can reduce gonadotrophin-induced follicle development in both intact and hypophysectomized ewes, findings which are more supportive of a direct ovarian action of inhibin.…”
Section: Discussioncontrasting
confidence: 58%
“…It should be emphasized that the present study concerns the long-term (>1 year) consequences of active immunization against inhibin, and that these are likely to be quite different from the acute effects on the pituitary-ovarian axis resulting from passive immunization against inhibin (Mann et al 1989, 1993, McNeilly et al 1991. The results confirm and extend previous evidence (Knight et al 1991b, Fray et al 1994, Bleach et al 1996 suggesting that the long-term stimulatory effect of IMM on follicle development may not be due exclusively to neutralization of the negative feedback action of inhibin on pituitary FSH.…”
Section: Discussionmentioning
confidence: 97%
“…To validate the electrochemiluminescence immunoassay and RIA of steroids, pooled follicular fluid and serum of ovariectomized cows were made steroid free by charcoal treatment [29]. Serial dilutions of estradiol, testosterone, progesterone, and 17-hydroxyprogesterone (Sigma-Aldrich) were prepared by using steroid-free follicular fluid or serum as diluents.…”
Section: Hormone Assaysmentioning
confidence: 99%
“…Selection of follicles is thus considered to be a systemically controlled process, regulated by the action of gonadotropins (primarily FSH), and modulated by intrafollicular factors such as IGF and its binding proteins [3][4][5]. However, although there is compelling evidence for this indirect, endocrine loop [2,6,7], and although it can explain how subordinate follicles fail to complete development, it is less clear how such a system could ensure that only the correct, species-specific number of follicles become dominant within the ovary in the first instance.…”
Section: Introductionmentioning
confidence: 99%